The comparative exploration of mobile money services in inclusive development - Simplice Asongu; Ndemaze Asongu (African Governance and Development Institute (AGDI), 2017)
Purpose- We respond to some challenges in the transition to Sustainable Development Goals by examining the correlations between mobile and inclusive development (quality of growth, poverty and inequality) in 93 developing countries for the year 2011. Design/methodology/approach- Mobile money service entails: `mobile used to pay bills' and `mobile used to receive/send money'. Interactive Ordinary Least Squares are employed. Findings- The following findings are established. First, increasing use of the mobile phones to pay bills: is positively linked to `quality of growth' in lower-middle income countries (LMIC) and negatively correlated with inequality in Latin American countries (LA). Second, growing use of mobile phones to send/receive money is negatively associated with poverty in Asia and Pacific (AP) and Central and Eastern Europe (CEE). Originality/value- Macroeconomic data on mobile money service is scarce. No study to the best of our knowledge has used this macroeconomic mobile money service data before.
Keywords: G20; O40; I10; I20; I32; 330; Mobile money services; Quality of growth; poverty; inequality